On-farm management practices against rice root weevil (Echinocnemus oryzae Marshall) - Pandey, Rakesh; Chaturvedi, Ajit Kumar; Chaudhary, Rudal Prasad; Prasad, Rajendra (Agriculture and Natural Resources, 2017)
Rice is the staple food of over half the world's population and occupies almost one-fifth of the global cropland under cereals. The rice root weevil, Echinocnemus oryzae Marshall, (Coleoptera: Curculionidae) has posed a problem in paddy cultivation areas in India. The damage by this root weevil results in a significant decrease in root and shoot biomass and ultimately the yield of rice plants. Studies were conducted to test the effective management practices of rice root weevil using a seedling treatment with chlorpyriphos alone and in combination with a soil application of chlorpyriphos, fipronil and cartap hydrochloride during 2013 and 2014. The benefit:cost (B:C) ratio was also determined from the marketable yield and cost of treatments incurred in the technology to justify the economic viability of the appropriate technology management against E. oryzae. Reductions in tillers/hill (35.2% and 26.27%) and, in panicles/hill (44.0% and 31.96%) were observed during 2013 and 2014, respectively. The least number of root weevils (3.67 and 3.13) were observed in comparison to no root weevil management practice (23.53 and 32.53) during 2013 and 2014, respectively, from the treatment of seedlings prior to transplanting with chlorpyriphos at 3 mL/L of water followed by soil application with cartap hydrochloride at 20 kg/ha. The highest numbers of tillers/hill (25.00 and 23.60), numbers of panicles/hill (20.00 and 19.40), yield (5.41 t/ha and 4.57 t/ha) and B:C ratio (1.75 and 1.48) were also observed from the same treatment during 2013 and 2014, respectively.